Optimisation of antithrombin resistance assay as a practical clinical laboratory test: Development of prothrombin activator using factors Xa/Va and automation of assay. (13th February 2018) - Tamura, S.; Suga, Y.; Tanamura, M.; Murata‐Kawakami, M.; Takagi, Y.; Hottori, Y.; Kakihara, M.; Suzuki, S.; Takagi, A.; Kojima, T.
Abstract: Introduction: Antithrombin resistance (ATR) is a novel thrombotic risk in abnormal prothrombins. A manual ATR assay using Oxyuranus scutellatus (Ox) venom as a prothrombin activator was established for detecting antithrombin‐resistant prothrombin. However, this assay was limited because of Ox snake venom availability and its throughput capacity. Here, we have improved the ATR assay using bovine factors Xa and Va (FXa/Va) as prothrombin activators and have optimised assay conditions for an automated instrument (ACL TOP 500). Methods: Diluted plasma was incubated with a prothrombin activator mix (phospholipids, CaCl2, and bovine FXa/Va), followed by inactivation with antithrombin for 10, 20 and 30 minutes. We added a chromogenic substrate S‐2238, and assessed changes in absorbance/min at 405 nm. We also adapted assay conditions for ACL TOP 500. Results: Optimum conditions for FXa/Va treatment were 6.25% phospholipids, 5 mM CaCL2, 0.01 μg/mL FXa and 0.1 μg/mL FVa. ATR assay kinetics with the FXa/Va activator was comparable with that with the Ox activator in heterozygous reconstituted plasma with the recombinant wild‐type or antithrombin‐resistant prothrombin. Using ACL TOP 500, optimum conditions for the FXa/Va treatment were 10.0% phospholipids, 5 mM CaCl2, 0.02 μg/mL FXa and 0.2 μg/mL FVa. The automated ATR assay with the FXa/Va activator demonstrated good detectability for antithrombin‐resistant prothrombin in plasma from a heterozygous carrier with prothrombin Yukuhashi or Belgrade. Conclusion: We optimised the ATR assay with the FXa/Va activator and adapted the assay for ACL TOP 500; the assay showed the ability to clearly detect antithrombin‐resistant prothrombin in manual and automated procedures.